A Case of Anaplastic Oligodendroglioma With Extensive Extraneural Metastases Imaged With FDG PET. (December 2017) - Ambinder, Emily B.; Rowe, Steven P.
Abstract : Abstract: A 28-year-old man with history of anaplastic oligodendroglimoma in the left frontal lobe presented with worsening right leg weakness 2 months after surgical resection. MRI of the brain and spine demonstrated a new mass in the left parietal lobe, as well as extraneural osseous metastases. FDG PET scan subsequently showed widespread extraneural metastatic disease. Extraneural metastases from primary brain tumors are a rare occurrence, although anaplastic oligodendroglioma has a propensity for spreading in such a manner. FDG PET can effectively stage patients with extraneural metastases from anaplastic oligodendroglioma by detecting metastatic disease in sites such as the skeleton and liver.